Stand and deliver Lean on me - Avildsen, John G., 1936-; Twain, Norman; Schiffer, Michael, 1948-; Menendez, Ramon; Musca, Tom.; Freeman, Morgan; Todd, Beverly, 1946-; Guillaume, Robert; North, Alan, 1920-2000.; Tigpen, Lynne; Olmos, Edward James; Phillips, Lou Diamond, 1962-; et al. (Burbank, Calif. : Warner Home Video, 2007)
Lean on me: A bat-and-bullhorn wielding principal in New Jersey turns a failing school around with his tough love methods.
Stand and deliver: A teacher in a Los Angeles barrio inspires his students to excel at math and to pass the Calculus Advanced Placement Test.
Lean on me directed by John G. Avildsen ; produced by Norman Twain ; written by Michael Schiffer.
Stand and deliver directed by Ramon Menendez ; produced by Tom Musca ; written by Ramon Menendez and Tom Musca.
Lean on me: Morgan Freeman, Beverly Todd, Robert Guillaume, Alan North, Lynne Tigpen.
Stand and deliver: Edward James Olmos, Lou Diamond Phillips, Rosana De Soto, Andy Garcia.
MPAA rating: Rated PG-13 (Lean on me).
MPAA rating: Rated PG (Stand and deliver).
Keywords: Clark, Joe, -- 1939 May 7- -- Drama; Escalante, Jaime -- Drama; Urban schools -- Drama; Problem youth -- Drama; High school principals -- Drama; High school teachers -- Drama; Mathematics teachers -- Drama; Hispanic American high school students -- Drama; Biographical films